National Elections and Political Apathy: A Comparative Study of Voter Turnout in the 2019 General Elections of Nigeria and South Africa - Nweke, Kenneth; Etido-Inyang, Eunice (Advances in Social Sciences Research Journal, 2020)
This research examines the impact of political apathy on electoral participation in Nigeria and South Africa in the 2019 general elections. The paper determined the causes of political apathy, its impact on the electoral process as well as its trend (voter turnout) in the general elections of 2019 in Nigeria and South. This research was borne out of the need to address the increasing rate of political apathy, especially voter turnout in both democratic nations. The research argued that the causes of political apathy, particularly poor voter turnout in the two countries are attributable to political marginalisation, corruption, lack of trust in the electoral process, political violence and militarisation of the electoral system. The research further found that there is no significant difference in the nature and trend of the political apathy (voter turnout) in both countries. The Rational Choice Theory (Downs, 1957) and the Democratic Deprivation Theory (Ebenezer, 2017) were used to theoretically justify the potentials of political apathy in undermining democratic participation. This study used descriptive research design to determine the impact of political apathy on the 2019 national elections in both countries. Trends and nature of political apathy, particularly voter turnout in the two countries were ascertained using secondary data and the analysis was based on content analysis in view of the historical trends and nature of the research. The research concluded that there is an obvious decline in political participation in both countries due to lack of trust in the electoral process, among others, which has largely undermined the interest of the electorate in the political systems of both countries. This research, therefore, recommends that political elite in both countries should be transparent, honest, responsible and responsive in order to encourage voter turnout in both countries at future national elections. A free, fair and credible electoral process, the study also recommended, would help rebuild citizens’ confidence in both countries’ electoral processes.